Sydenham’s chorea - clinical and evolutive characteristics - Terreri, Maria Teresa Ramos Ascensão (2002)
CONTEXT: During the last 12 years we have observed anincreaseinthefrequencyofSydenham’schorea in our country.Wehave observed that some of our patients have presented recurrence of the chorea despiteregulartreatmentwithbenzathinepenicillin. OBJECTIVE: The aim of our study was to evaluate clinical and evolutive characteristics of Sydenham’s chorea in a group of patients followed in our Pediatric Rheumatology Unit. TYPE OF STUDY: Retrospective study. SETTING: Section of Pediatric Rheumatology - Discipline ofAllergy,ClinicalImmunologyandRheumatology - Department of Pediatrics - UNIFESP - EPM. PARTICIPANTS: Two hundred and ninety patients with rheumaticfeverfollowedbetween1986and1999. METHODS: We reviewed the records of 290 patients with rheumatic fever followed between 1986 and 1999. All patients were diagnosed according to the revised Jones criteria (1992). We included 86 patients that presented Sydenham’schorea as one of the major criteria (one or more attacks) and evaluated their clinical and evolutive characteristics as well the treatment. RESULTS: Fifty-five patients were girls and 31 were boys. The mean age at onset was 9.7 years and mean follow-upperiodwas3.6years.The86Sydenham’s chorea patients presented 110 attacks of chorea. Weobservedisolatedchoreain35%ofthepatients, and 25 (29%) presented one or more recurrences. We included only 17 of the 25 patients for further analysis, withatotal of 22 recurrences of which 14 wereattacksofchorea,becauseitwasnotpossible to precisely detect the interval between attacks in theotherpatients.Theapproximateintervalbetween the attacks ranged from 4 to 96 months. In 71% of the patients there was no failure in the secondary prophylaxis with benzathine penicillin, which was performedevery3weeks. CONCLUSION: Despite the regular use of secondary benzathine penicillin prophylaxis, children with rheumatic fever have a high risk of Sydenham’s chorea recurrence.